PERANAN PENYAMPAIAN DAN OPERASI JASA, TERHADAP KEPUASAN PASIEN SERTA DAMPAKNYA PADA REPUTASI RUMAH SAKIT - indra maulana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This study aims to determine the factors that have roles to patient satisfaction at the Bhakti Husada II Hospital Purwakarta. The variables used are service delivery elements (X1), service delivery elements (X2) on patient satisfaction (Y) and their impact on company reputation (Z) at Bhakti Husada II Hospital Purwakarta. This research is a quantitative research with survey method. The population in this study was inpatients at Bhakti Husada II Hospital Purwakarta. Data collection techniques using a questionnaire that has been tested for validity and reliability. The results of this study indicate that the two independent variables significantly influence patient satisfaction. The variable service delivery element and service operation variable variable with a significant level of 0,000.